TrACES of time: Transcriptomic Analyses for the Contextualization of Evidential Stains – towards estimating the time of deposition. (December 2022) - Gosch, A.; Bhardwaj, A.; Courts, C.
Abstract: In forensic casework, identifying the donor of a biological trace is oftentimes not sufficient to reconstruct the true course of events and additional knowledge regarding the context of trace deposition is required. The human transcriptome in biological material comprises a multidimensional complex of information including composition and condition of a biological fluid/tissue. In this study we aim to assess the potential of transcriptomic analyses to predict the time of day of biological trace deposition by identifying mRNA marker combinations most suitable for time of day predictions.